(untitled) (Journal of Applied and Natural Science, 2015)
Eight medicinal plants viz., Sinduri, Bixa orellana (Bixaceae); Dalchini, Cinnamomum zelanicum (Lauraceae); Camphora, Cinnamomum camphora (Lauraceae); Gular, Ficus racemosa (Moraceae); Arjun, Terminalia arjuna (Combretaceae); Nagkesar, Messua ferrea (Calophyllaceae); Sarpgandha, Rauwolfia serpentina (Apocynaceae); Putranjeeva, Putranjeeva roxburghii (Euphorbiaceae) at 5% and 10 % concentrations were tested for the feeding against larvae of Spodoptera litura and Spilarctia obliqua. At 10% conc. C.camphora (hexane, diethyl ether, and acetone) was found extremely antifeedant against the larvae of both insects (S.litura and S.obliqua) while C.zeylanicum (hexane, diethyl ether, and acetone) and P.roxbughii (diethyl ether, and acetone), B.orellana (Acetone) showed extremely antifeedant activity only against the larvae of S.litura. At 5% concentration, the same plants were also effective against the larvae but their efficacy was less than at 10% concentration. The observation showed promising results with these plant extracts against the feeding and management of these two insect pests of agricultural importance.